IMPLEMENTASI NILAI-NILAI SOSIAL PADA EKSTRAKURIKULER PRAMUKA DI MADRASAH ALIYAH NEGERI 1 LOMBOK BARAT - M. Khaerozi; Hamidsyukrie ZM; Suud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the implementation of social values ​​in scout extracurricular activities at Madrasah Aliyah Negeri 1 West Lombok. This research uses a qualitative approach with a case study method. The types of data used are primary data and secondary data. ssData comes from subjects and informants. The data collection techniques used were observation, interviews and documentation. Data were analyzed using Miles and Huberman data analysis techniques. The results of the research show that there is an implementation of social values ​​that have been implemented in scout extracurricular activities at MAN 1 West Lombok, namely: 1) Love, including an attitude of devotion to God such as carrying out the five daily prayers in congregation during camp which is formed from values devotion.; 2) Responsibility includes having an attitude of feeling of ownership towards a task that is given and must be completed well which is formed by the value of a sense of belonging.; 3) Harmony in life includes being fair in sharing consumption during camping activities which is formed on the value of justice.